Mapping change in self narrative after prolonged exposure therapy: An exploration in recovery from functional dissociative seizures - Jon D. Perkins; Sam Meekings (Epilepsy & Behavior Reports)
This study explored self-narrative transformations in a participant with functional dissociative seizures (FDS) following prolonged exposure therapy. The study aimed to establish emergent themes that indicated psychological challenges and the subsequent psychological shifts that accompany FDS resolution. Two interviews were held one month apart. An open-ended questionnaire was employed in the first interview, followed by a structured questionnaire based on previous findings in the second. Thematic analysis was used to explore the narrative of the transcribed interviews and extract themes. Themes constituted four or more references to the same topic during the interviews. Six main themes were identified. These were, in order of the most prevalent, Emotional and Cognitive Insights (29 %), Understanding and Negotiating Fear (24 %), Detachment and Attachment (21 %), Self-Management and Resolution (18 %), Physiological Insights (13 %) and Shifting Relationships and Social Interactions (11 %). Narratology reveals key features of an individual’s story and offers insight into their psychological experience. In FDS patients, where psychological disturbance may be a causal factor for symptoms, the formation of a coherent self-narrative can be mapped from pathology through to symptom resolution. In doing so, this process identifies important possible narrative markers underlying the psychological processes involved in FDS.